2017
DOI: 10.1007/s00210-017-1422-z
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent effects of omecamtiv mecarbil on cell shortening of isolated canine ventricular cardiomyocytes

Abstract: Omecamtiv mecarbil (OM) is a myosin activator agent developed for the treatment of heart failure. OM was reported to increase left ventricular ejection fraction and systolic ejection time, but little is known about the effect of heart rate on the action of OM. The present study, therefore, was designed to investigate the effects of OM on unloaded cell shortening and intracellular Ca ([Ca]) transients as a function of the pacing frequency. Isolated cardiomyocytes were stimulated at various frequencies under ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 27 publications
9
25
0
Order By: Relevance
“…5) and suggests the presence of substantial noise in the expression of genes that participate in the β-adrenergic signaling pathway. Cardiomyocyte responses to OM were consistent with other recent reports (3,7), including the observation that OM increases contractility at the expense of diastolic function.…”
Section: Discussionsupporting
confidence: 90%
“…5) and suggests the presence of substantial noise in the expression of genes that participate in the β-adrenergic signaling pathway. Cardiomyocyte responses to OM were consistent with other recent reports (3,7), including the observation that OM increases contractility at the expense of diastolic function.…”
Section: Discussionsupporting
confidence: 90%
“…Similar effects were obtained under in vivo conditions in anesthetized dogs and rats, where omecamtiv mecarbil displayed more pronounced action in the canine hearts [22]. However, the effects of omecamtiv mecarbil on cell shortening are concentration-and frequency-dependent in canine ventricular cells [40]. As demonstrated in Fig.…”
Section: Effect On Cell Shorteningsupporting
confidence: 78%
“…Biochemical kinetic experiments have suggested that OM does not affect the actomyosin-detachment rate during cycling 1 , 6 , which is at odds with our findings. However, studies of tension development and relaxation rates of cardiac muscle preparations have indicated that detachment may be slowed by OM 11 , 12 , 34 . The previous biochemical conclusions 1 , 6 were based on the measurement of the rate of ADP release (the step that limits the rate of actin detachment at physiological ATP) from an AM·ADP complex formed by adding ADP to the rigor, AM complex in isolated actomyosin 1 , 6 , 9 Our results indicate that the step that limits actin detachment is not accessible by simply adding ADP, but occurs earlier in the cycle and may not be on the conventional ATPase pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%